Wear and friction behaviour of Cu-Gr-B4C composites and correlating to the topographical characteristics - Kumar M.; Ankit; Majhi M.R.; Chaturvedi R.K. (My University, 2025)
The mechanical and tribological characteristics are important in applications such as bearing linings, bushings, and electrical contacts. In the current experiment, copper-chromium matrix composites reinforced with graphite (Gr.)-boron carbide (B4C) [at 1.5, 3, and 4.5 wt%] were made using powder metallurgy (P/M) process. As reinforcements, equal amounts of Gr and B4C were utilized. The microstructural characteristics of the sintered composites have been investigated using analytical techniques such as EDS mapping analysis, x-ray diffraction, and scanning electron microscopy (SEM). The composites with a copper matrix displayed a homogeneous distribution of the reinforcement phase within the material. The pin-on-disc tribometer was used to conduct dry sliding wear tests with loads ranging from 10 to 40 N, sliding speeds of 1-3 m s−1, and fixed sliding distances of 2 km. The hardness is 97.3 HV with 3 wt% of each graphite and B4C reinforcement, which is 70.1% harder than pure copper (57.2 HV). It has been discovered that the wear rate and COF of composites decrease as the quantity of reinforcing rises—the composite with 4.5 wt% graphite and 4.5 wt% B4C exhibits the least amount of wear. The wear rate showed a rising trend with the applied load and sliding velocity across every material. The study of the deteriorated surface also reveals that delamination is the primary wear mechanism for pure Cu specimens. B4C and graphite-reinforced composites have been subjected to abrasives, oxidative and delamination wear modes. © 2024 IOP Publishing Ltd.